Determination of leaf area index for oil palm plantation using hemispherical photography technique - Awal, Md. Abdul; Wan Ismail, Wan Ishak; Bockari-Gevao, Sakr Marvin (Universiti Putra Malaysia Press, 2010)
The present conventional (destructive) method used in determining LAI is laborious, difficult and time consuming. Thus, an image-based measurement using camera system with fish eye lens offers an alternative means for an accurate indirect measurement of LAI in oil palm. In this study, a methodology was developed to improve the leaf area index of the oil palm determination using hemispherical photography as an indirect method. A set of true LAI data, collected using the destructive method, were used as a reference to calibrate the LAI measurements obtained by the hemispherical photography. A good relationship (r = 0.85) was found between age of palm and hemispherical photographic LAI. However, the estimated LAI obtained by the hemispherical photographic method was underestimated as compared to the destructive method. Some means of calibration was necessary to determine the relationship between the actual LAI and the hemispherical photographic LAI. It was necessary to multiply the LAI value from 5 years to 16 years, by a clumping factor of 2.14 for 5 to 9 year old palms, 2.33 for 10 to 14-year old palms and 2.37 for above 15-year old palms to calculate the accurate LAI values. For palms which are less than 5 year old (i.e. 2 to 3 years in this study), the photography LAI value was equal to the calculated LAI value. This proposed that correction factors would solve this underestimation effect. In addition, two equations were also proposed to estimate the true LAI from the Photographic LAI for immature and mature oil palm plantation.